Why humans evolved blue eyes - Bressan, Paola (Frontiers in Psychology, 2025)
A surprising number of humans are equipped with a subpar eye model—featuring pale, colorful irides that are nowhere as good as the original dark ones at guarding the retina from sunlight and do, in fact, raise one’s risk of eye disease. Here I apply evolutionary theory to understand why. I propose that the allele for human blue eyes, which arose just once, managed to spread from one individual to millions at an astonishing speed because it is a greenbeard. “Greenbeards”—imaginary genes, or groups of genes, that produce both a green beard and a behavior that favors other bearers of a green beard—have been deemed exceedingly unlikely to show up in the real world. And yet, as individuals who prefer blue eyes are more inclined to mate with blue-eyed partners and invest in blue-eyed offspring, any blue-eye preference (whether random or arising from the bias for colorful stimuli shared by all recognition systems) becomes rapidly linked to the blue-eye trait. Thus, blue eyes gain an edge by working like a peacock’s colorful tail and a nestling’s colorful mouth: twice self-reinforcing, “double runaway” evolution via sexual and parental selection. The blue-eye ornament gene, by binding to a behavior that favors other bearers of the blue-eye ornament gene, is ultimately recognizing and helping copies of itself in both kin and strangers—and greatly prospering, just like theory predicts.